The impact of ecocommunity-based tourism development - Oman Sukmana (Masyarakat, Kebudayaan dan Politik, 2022)
Batu City as a tourism city in Indonesia has a significant impact on its citizens. This study aims to describe the impact of the development of Batu City as a tourism city through the Ecocommunity-Based Tourism (ECBT) model on job growth and poverty reduction. This was qualitative research, in which the technique of collecting data was done through documentation, interviews, and observation. The results showed that Batu City was developed as a tourism city based on ECBT which is a combination of Ecotourism (ET) and Community-Based Tourism (CBT). The development of Batu City as a tourism city has a positive effect on employment growth of 1,074 types of employment in 2013 and increased to 6,183 types of employment in 2017. The increase in employment in the tourism industry sector also has an impact on reducing poverty levels, with the percentage of poor people in Batu City decreasing from 4.67 percent in 2013 to 4.31 percent in 2017. Other research findings also show that the migration of job seekers out of Batu City tends to be low, while the migration of job seekers into Batu City tends to be high. This study concludes that the development of tourism in Batu City is effective in creating jobs and reducing poverty levels.